Studi Eksperimen: Edukasi Sleep Hygiene dan Terapi Kognitif Perilaku terhadap Kecanduan Gawai Remaja di Kota Jambi - Nurlinawati Nurlinawati; Riska Amalya Nasution; Meinarisa Meinarisa; Yuliana Yuliana (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Device users in Indonesia are dominated by teenagers. Excessive use of gadgets can lead to gadget addiction and the risk of experiencing mental health problems. The purpose of this study was to determine the effect of sleep hygiene education and cognitive behavioral therapy on adolescent device addiction in Jambi City. The research design used was "quasi experimental pre-post test with control group". The number of samples in this study were 130 people with 65 people in the intervention group, and 65 people in the control group. The sampling method is purposive sampling. The measurement tools used in this study were the internet addiction test (IAT) questionnaire and the sleep quality questionnaire: the Pittsburgh sleep quality index (PSQI). The statistical test used is the paired sample t-test. The results showed that there was a significant effect of providing sleep hygiene education and cognitive behavioral therapy on adolescent gadget addiction p=0.000 (p <0.05) in the intervention group. Whereas in the control group which was only given sleep hygiene education there was also a significant effect p=0.013 (p <0.05). Providing nursing interventions needs to be carried out for all adolescents by nurses in the community to prevent device addiction from occurring and also to help the condition of adolescents who are addicted to devices.